2008
DOI: 10.1097/adm.0b013e31818d8916
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Sensation Seeking, Parental History of Alcohol Problems, and Current Alcohol and Tobacco Use in Adolescents

Abstract: Objectives-This study attempted to evaluate whether impulsive sensation seeking mediated the relationship between parental alcohol problems and offspring alcohol and tobacco use.Methods-Participants were Connecticut high school students (n = 2733) completing a survey of high-risk behaviors. Variables of interest included past month alcohol use, past month binge alcohol use, frequency of past month alcohol use, past month tobacco use, having a biological parent with an alcohol problem, and score on the impulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 42 publications
6
53
0
1
Order By: Relevance
“…Possible limitations relate to the sample, as this sample is not random; however, demographics were consistent with those reported in the 2000 Census of Connecticut residents between the ages of 14–18 (Bureau, 2000; Schepis et al, 2008). Moreover, these data may not reflect current prevalence rates, and further work is needed to better understand forms of gambling that are growing in popularity, including gambling via social media.…”
Section: Discussionmentioning
confidence: 63%
“…Possible limitations relate to the sample, as this sample is not random; however, demographics were consistent with those reported in the 2000 Census of Connecticut residents between the ages of 14–18 (Bureau, 2000; Schepis et al, 2008). Moreover, these data may not reflect current prevalence rates, and further work is needed to better understand forms of gambling that are growing in popularity, including gambling via social media.…”
Section: Discussionmentioning
confidence: 63%
“…Full recruitment and consenting procedures and sample characteristics have been described in detail previously (Schepis et al 2008). Briefly, invitations to participate were extended to all 4-year and non-vocational or special-education high-schools in the state of Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…Less than 1% of student refused to participate. Detailed descriptions of the recruitment procedures, variables, and classification of responses were previously presented (Potenza et al 2011; Schepis et al 2008; Yip et al 2011). The survey consisted of 154 questions assessing a broad range of demographic characteristics, health/functioning measures, gambling (defined to students as “any game you bet on for money or anything else of value”), substance use and other risk behaviors, and included items derived from established measures (e.g., Massachusetts Gambling Screen, Shaffer et al 1994) and national surveys (e.g., Youth Cihild Risk Behavior Survey, Eisenmann et al 2002; and National Gambling Impact Study 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research has demonstrated the relevance of impulsive personality to substance use risk, because impulsive traits have been shown to relate to substance use/problems both concurrently and prospectively (Ball et al, 1994;Carlson et al, 2010;Corbin et al, 2011;Grau & Ortet, 1999;Horvath et al, 2004;Lynam & Miller, 2004;Milich et al, 2000;Miller et al, 2003;Puente et al, 2008;Schepis et al, 2008;Sher et al, 2000;Verdejo-García et al, 2007). Further support for impulsivity's contribution to the development of problematic substance use comes from studies of individuals identified as at risk for substance dependence based on family history, who have been found to be more impulsive on a variety of measures (Acheson et al, 2011;Handley et al, 2011;Tarter et al, 2003).…”
mentioning
confidence: 98%